Pengaruh Literasi Halal, Religiusitas, Halal Awareness Terhadap Minat Beli Konsumen pada Restoran Bersertifikat Halal pada Generasi Z di Jabodetabek: Halal Industry - Anjeli, Anjeli Wijaya; Anita Priantina (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to investigate the influence of halal literacy, religiosity, and awareness of halal on consumer buying interest in halal certified restaurants in the Jabodetabek area, with a focus on Generation Z. Data was collected through a survey targeting 162 respondents using a scale of 1 to 6. Testing was carried out using the Smart PLS V.3 analysis tool and the Structural Equation Modeling (SEM) analysis approach. The results of the analysis show that halal literacy has a positive but not significant influence on consumer buying interest, while religiosity and halal awareness will have a positive and significant influence on consumer buying interest. These findings indicate that religious understanding and awareness of halal play an important role in influencing consumer shopping behavior, especially in the context of halal certification. The implications of these findings can help halal food and beverage industry stakeholders in developing more effective marketing strategies to attract and retain their potential customers amidst increasingly fierce competition in the industry.